Quantum plasmon model for the terahertz photoconductivity in intrinsic semiconductor nanowires. (4th September 2017) - Yan, Jie-Yun
Abstract: A quantum plasmon model for the terahertz photoconductivity in intrinsic semiconductor nanowires is developed. The classical plasmon model assumes the excited electron in semiconductors feels a restoring force generated by a harmonic-oscillator potential. Although it is successfully applied to explain the terahertz photoconductivity in semiconductor nanowires, the classical treatment of the potential weakens accurate theoretical analysis. Here I treat the potential in a full quantum way and present an exact analytical formula for photoconductivity. The formula not only gives more reasonable photoconductivity, but also has the same conciseness when compared with that of the classical plasmon model. The validity of the quantum plasmon model is proved independently by numerical calculations in real space.